Political Analysis of the Discourse of Ernesto Laclau: A Proposal for Trans-disciplinary Social Research - Hernán Fair (Íconos)
This article develops a proposal for trans-disciplinary collaboration that offers some theoretical tools that both complicate and strengthen the operational capacity of the perspective of Ernesto Laclau. The objective is to deconstruct a useful, rigorous and valid methodology for the political analysis of discourse without loosing the vision of social transformation. The hope is to contribute to the construction of a program of social research about the theory of hegemony from our region.